Penerapan Model Pembelajaran Teams Games Tournament Untuk Meningkatkan Keaktifan Belajar Peserta Didik Kelas IV Sekolah Dasar - Noviana Noviana; Ferina Agustini; Yustina Gunarti; Ikha Listyarini (Departement of Mathematics Education, 2024)
This research aims to provide a picture of the application of the Teams Games Tournament learning model in increasing students' active learning. This type of research is classroom action research (PTK) which is carried out through 2 cycles, namely cycle I and cycle II. This research data was collected using observation and documentation techniques. The data analysis used is qualitative data analysis and quantitative data analysis. The subjects of this research were 30 grade IV students at SD Negeri Pedurungan Lor 02. The research results show that students' learning activity after implementing the Teams Games Tournament learning model has increased in each indicator. In cycle I, the average learning activity of students was 63.4%, then increased to 82.6%.